Citizen involvement in co-producing decentralised stormwater systems in Brussels. Issue 3 (3rd July 2021) - Dobre, Catalina Codruta; Ranzato, Marco; Moretto, Luisa
ABSTRACT: Co-production initiatives rely on citizens' contributions to create better public services. Although the existing literature has frequently focused on citizens' motivations to join co-production activities, few studies have investigated how and why citizen involvement might change during the co-production process. The article offers new insights about engagement in co-production by analysing a design initiative in Brussels, Ilot d'eau . Throughout the initiative, the four citizen collectives elaborated a specific decentralised stormwater system project that would be shared among the respective households. Even though each collective followed the same methodology, only two of the four projects reached the co-construction phase. The paper reveals how changes in citizen involvement in the process are impacted by the methodologies of interaction used and the citizens' previous experiences in co-production. Furthermore, by examining the premature withdrawal of two of the four collectives from the initiative, the study shows why some of the changes occurred. In particular, the ambivalent role played by the local municipality during the development of the initiative together with the mediation of the organising team emerge as key determinants influencing citizen involvement.